SALURAN PEMASARAN BUAH SALAK DI DESA BAWOLEU KECAMATAN TAGULANDANG UTARA KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Timotius Fernel Makinggung; Olly Esry Haryani Laoh; Martha Mareyke Sendow (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the marketing of salak fruit, analyze profits and marketing margins of zalacca, and analyze the farmer's share in each marketing channel of zalacca in Bawoleu Village. This research was carried out in Bawoleu Village, North Tagulandang District, Siau Tagulandang Biaro Regency. The sample selection is done purposevely and snowball method. Data collected are primary and secondary data. Primary data collection was carried out by direct interviews with 16 salak farmers and related marketing institutions. The data collected are the characteristics of respondents, the characteristics of salak fruit farming, prices at the level of farmers, traders, and consumers, as well as marketing institutions in marketing salak fruit. Secondary data obtained from the Internet through Google searching. The results showed that the marketing channels formed in the marketing of salak fruit in Bawoleu Village were 3 types of marketing channels, namely marketing channel I, which had a total cost of Rp. 575 / Kg, Marketing channel II the total cost of Rp 575 / kg, profit of Rp 15,675 / Kg and marketing margin of Rp 16,250 / Kg. Marketing channel III costs a total of Rp. 875 / Kg, Profits Rp. 375 / Kg, marketing margin Rp. 1,250 / Kg. The portion received by farmers (farmer share) in marketing channel I is 100%, marketing channel II is 18.75%, marketing channel III is 75%.*eprm*